1985
DOI: 10.1007/978-94-011-5939-5
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Meat Research

Abstract: All rights reserved. No part of this work covered by the copyright hereon may be reproduced or used in any form or by any means-graphic, electronic, or mechanical, including photocopying, recording, taping, or information storage and retrieval systemswithout written permission of the publisher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 91 publications
(226 reference statements)
0
3
0
2
Order By: Relevance
“…The presence of undesirable gel has been explained by Sams [14] and Pearson and Dutson [67]. Those authors demonstrated that the added collagen, in certain concentrations, can have a negative effect, causing shrinkage, especially when these products are submitted to high temperatures [68].…”
Section: Physical and Chemical Characterization Of Chicken Hammentioning
confidence: 96%
“…The presence of undesirable gel has been explained by Sams [14] and Pearson and Dutson [67]. Those authors demonstrated that the added collagen, in certain concentrations, can have a negative effect, causing shrinkage, especially when these products are submitted to high temperatures [68].…”
Section: Physical and Chemical Characterization Of Chicken Hammentioning
confidence: 96%
“…On the other hand that non-essential amino acid was dominated by glutamic and serine. Pearson and Dutson (1992) reported that at curing process, change happen as result of skin collagen protein and some certain amino acids denaturation changed chemically. But, an interesting matter that found in this study (Table 1), essential and non-essential amino acids detected same high on the broiler chicken, cattle and goat compare to references of Cshrieber and Gareis (2007).…”
Section: Results and Analysismentioning
confidence: 99%
“…It is seen from the data in Table 4 that L* increased in conjunction with the elevation of ice water treatment time. Consequently, the ice water level was reduced, exposing more shrimp on the surface and increasing the light reflection effect (Pearson & Dutson, 1985). The increase in the L* of the shrimp color was mainly due to the formation of ice crystals in the holding water containing the shrimp meat that resulted in a decrease in the level of ice water.…”
Section: Changes In Colormentioning
confidence: 99%